ASSOCIATIONS OF IL-6 -174G>C AND IL-10 -1082A>G POLYMORPHISMS WITH SUSCEPTIBILITY TO CELIAC DISEASE: EVIDENCE FROM A META-ANALYSIS AND LITERATURE REVIEW - AFLATOONIAN,Majid (2019)
ABSTRACT BACKGROUND: There has been little evidence to suggest that the IL-6 -174G>C and IL-10 -1082A>G polymorphisms are significantly associated with susceptibility to celiac disease. Thus, we performed the present meta-analysis to explore the potential association between these polymorphisms and celiac disease risk. METHODS: Eligible studies were searched in PubMed, Medline, Embase, Web of Science and CNKI database up to April 20, 2019. Odds ratios with 95% confidence interval were calculated to assess the potential associations. Moreover, we performed the heterogeneity, sensitivity, and publication bias tests to clarify and validate the pooled results. RESULTS: Overall, nine case-control studies involving five studies with 737 cases and 1,338 control on IL-6 -174G>C polymorphism and four studies with 923 cases and 864 controls on IL-10 -1082A>G polymorphism were selected. The pooled ORs showed that the IL-6 -174G>C and IL-10 -1082A>G polymorphisms were not significantly associated with increased risk of celiac disease under all five genetic models. There was no publication bias. CONCLUSION: To the best of our knowledge, this is the first meta-analysis summarizing all of the available studies on the association of IL-6 -174G>C and IL-10 -1082A>G polymorphisms with celiac disease. Our results suggest that the IL-6 -174G>C and IL-10 -1082A>G polymorphisms may not be associated with increased risk of celiac disease. Moreover, large and well-designed studies are needed to fully describe the association of IL-6 -174G>C and IL-10 -1082A>G polymorphisms with celiac disease.